Modern treatment of ALK-positive non-small cell lung cancer - D. A. Kharagezov; Yu. N. Lazutin; E. A. Mirzoyan; A. G. Milakin; O. N. Stateshny; I. A. Leyman; M. A. Gappoeva; V. N. Vitkovskaya; K. D. Iozefi (Южно-Российский онкологический журнал)
Lung cancer (LC) takes the first place in the structure of overall oncology in males. More than 1.8 million of new cases of lung cancer (LC) are registered each year worldwide. LC is the leading cause of cancer death in both developing and developed countries, and the 5 years survival rate is as low as 19 %. Many factors explain such unsatisfactory outcomes, including the LC diagnosis at an advanced stage, when the currently available treatments can rarely provide cure. Non-small cell lung cancer (NSCLC) with chromosomal rearrangement of anaplastic lymphoma kinase (ALK) is sensitive to targeted therapy with tyrosine kinase inhibitors (TKIs). Tumor cells containing ALK fusion are sensitive to TKIs – targeted drugs that have significantly improved the results of treatment of patients with ALK-positive NSCLC, half of whom survive more than 6.8 years after diagnosis. The number of patients with ALK-positive NSCLC varies, so ALK rearrangements are detected in about 3–7 % of lung adenocarcinomas, which accounts for up to 60.000 new cases of the disease annually worldwide. ALK-positive NSCLC is observed almost exclusively in adenocarcinomas associated with persons of younger age, male and never smoked or smoked a little. Patients with ALK-positive stage I–III NSCLC are shown treatment similar to patients with wild-type NSCLC, including surgery, radiation therapy, chemotherapy or multimodal treatment, depending on the stage of the tumor process. Numerous ALK TKIs have been developed in recent years, including alectinib, which is the current preferred first-line agent for patients who haven’t received therapy. The study of the mechanisms of resistance has led to the development of next-generation ALK inhibitors that better penetrate the central nervous system, actively affecting brain metastases. This review highlights the current state and prospects for the development of ALK-positive NSCLC therapy.